Elementary Teachers' Perceptions and Experiences Regarding Social-Emotional Learning in Ontario - Hajar Jomaa; Cheryll Duquette; Jessica Whitley (Brock University, 2023)
Social-emotional learning (SEL) is an essential part of students' learning journey. Teachers' perceptions of SEL have been associated with teaching outcomes and the effectiveness of its implementation in classrooms. In Ontario, SEL is a mandated component of some curricular areas. It is important to consider teachers' perceptions and experiences regarding SEL because a teacher who is confident in implementing SEL strategies may contribute to positive social, emotional, and academic outcomes for their students. This study explored teachers' perceptions and experiences regarding SEL before and during the COVID-19 pandemic. Three elementary teachers in Ontario implementing SEL practices took part in a semi-structured interview that followed a modified version of Seidman's (2019) three-interview protocol, and was informed by the CASEL (2021b) framework. Research findings reveal for the first time in the literature elementary teachers' perceptions and experiences on SEL during the COVID-19 pandemic in Ontario. The benefits and barriers of teaching SEL competencies to students were discussed, as were the SEL strategies implemented by the teachers and professional development received on it. Implications for practice were also described.